Validitas Buku Ajar dengan Pendekatan Kontekstual dalam Membelajarkan Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Sabri Sabri; Umar Kholil; Marzuki Ahmad (Elementary Teacher Education Program, Majalengka University, 2023)
The low creative thinking ability of elementary school students is the main research problem. This is because the learning that is carried out tends to be conventional and the lack of textbooks that support students to be active and creative in learning. A learning that supports student activity in learning is a contextual learning approach. By using textbooks that are relevant to students' situations, it is hoped that students' creative thinking skills will develop well through the learning process. The purpose of this study was to describe the validity of developing textbooks with a contextual approach in teaching elementary school students' creative thinking skills. The research method is to apply the ADDIE model which in this stage will specifically describe the development stage. The development of textbooks was carried out by giving assessments from 4 validators to textbooks in terms of format, language and content of textbooks. Analysis of the results of the assessment of the 4 validators showed that the average percentage score of textbooks on the format aspect was 77.00 (high), the language aspect was 85.83 (high) and the content aspect was 81.11 (high). Furthermore, the overall average is 81.31 (high). From the achievement of the average percentage score obtained, it was concluded that textbooks with a contextual approach in teaching students' creative thinking abilities fulfill aspects of validity and can be implemented in Civics learning for elementary school students.